Association between dynapenic obesity and risk of cardiovascular disease: The Hisayama study - Yu Setoyama; Takanori Honda; Takahiro Tajimi; Satoko Sakata; Emi Oishi; Yoshihiko Furuta; Mao Shibata; Jun Hata; Takanari Kitazono; Yasuharu Nakashima; Toshiharu Ninomiya (Journal of Cachexia, Sarcopenia and Muscle)
Abstract Background Dynapenic obesity is a condition characterized by high adiposity levels combined with muscle dysfunction. Although high adiposity and muscle loss/dysfunction are thought to synergistically increase the risk of cardiovascular disease (CVD), few studies have addressed the association between dynapenic and sarcopenic obesity and CVD. We aimed to investigate the association of dynapenic obesity with incident CVD events using the data from a population‐based prospective longitudinal study in Japan. Methods A total of 2490 community‐dwelling Japanese aged 40–79 years (42.5% males, mean age 57.7 ± 10.6 years) without a history of CVD were followed up for a median of 24 years. Handgrip strength was classified as low, medium, or high by age‐ and sex‐specific tertiles. Body mass index (BMI) levels were categorized as lean (<18.5 kg/m2), normal (18.5–24.9 kg/m2), or obese (≥25.0 kg/m2). Dynapenic obesity was defined as having both low handgrip strength and obesity. The outcomes were defined as the first‐ever development of CVD (defined as stroke or coronary heart disease). The hazard ratios (HRs) and their 95% confidence intervals (CIs) for the development of CVD were estimated using a Cox proportional hazards model, in which participants with high handgrip strength and normal BMI were used as a reference group. Mediation analyses used serum high‐sensitivity C‐reactive protein (hs‐CRP) and homeostatic model assessment for insulin resistance (HOMA‐IR) as mediators. Results During the follow‐up period, 482 participants developed CVD events (324 cases of stroke and 209 of coronary heart disease). The multivariable‐adjusted risk of CVD increased significantly among participants with dynapenic obesity compared with the reference group (HR 1.49, 95% CI 1.03–2.17). An analysis by age groups showed a further increase in the risk of CVD among participants with dynapenic obesity aged less than 65 years (HR 1.66, 95% CI 1.04–2.65). In mediation analyses for participants aged less than 65 years, serum hs‐CRP was shown to be a significant mediator explaining 13.8% of the association between dynapenic obesity and the development of CVD, while HOMA‐IR explained 12.2% of this relationship. Conclusions Dynapenic obesity was a significant risk factor for the development of CVD in a general Japanese population. This association was more pronounced among those aged <65 years. Inflammation, and possibly glucose metabolism, might partly mediate this association. Our findings suggest that preventing muscle dysfunction as well as appropriate weight control, especially in middle‐age, are important for preventing the development of CVD.